2022
DOI: 10.3390/oxygen2020008
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Field-Based Extraction of Total Polyphenols from Sideritis raiseri Using Hydroethanolic Mixtures

Abstract: Polyphenols are an important class of compounds, due to their excellent antioxidant properties. Lately, much effort has been placed into developing new extraction techniques and optimizing them, so that polyphenols can be retrieved more efficiently from the plant materials. One of the most recent advances in extraction techniques is pulsed electric field extraction (PEF). This new technique is environmentally friendly and has the potential to maximize the recovery of compounds from plant tissues. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…46 Ethyl acetate is known for its effectiveness in extracting terpenoids, 47 our research goal extended beyond terpenoids isolation alone. Ethanol, a more polar solvent than ethyl acetate, allows for the extraction of a wider array of bioactive compounds, including polyphenols, 48 flavonoids 49 and other polar constituents in addition to terpenoids which are of significant interest in our investigation. In accordance with our research, bicyclo[4.3.0]nonane, 2,2,6,7-tetramethyl-7-hydroxy have also been identified in the methanol extract of Dicliptera roxburghiana , demonstrating appreciable anticancer characteristics, 50 additionally, this compound has been found in Nicotiana tabacum 51 and in the leaf and stem of Marsilea quadrifolia (L.).…”
Section: Discussionmentioning
confidence: 99%
“…46 Ethyl acetate is known for its effectiveness in extracting terpenoids, 47 our research goal extended beyond terpenoids isolation alone. Ethanol, a more polar solvent than ethyl acetate, allows for the extraction of a wider array of bioactive compounds, including polyphenols, 48 flavonoids 49 and other polar constituents in addition to terpenoids which are of significant interest in our investigation. In accordance with our research, bicyclo[4.3.0]nonane, 2,2,6,7-tetramethyl-7-hydroxy have also been identified in the methanol extract of Dicliptera roxburghiana , demonstrating appreciable anticancer characteristics, 50 additionally, this compound has been found in Nicotiana tabacum 51 and in the leaf and stem of Marsilea quadrifolia (L.).…”
Section: Discussionmentioning
confidence: 99%
“…All information regarding the analyses of the extracts for their TPC, total flavonoid content (TFC), total anthocyanins (TA), ascorbic acid content, and their antioxidant activity (assessed using the DPPH free radical scavenging assay and the FRAP assay) and color analysis are given in detail in Supplementary Materials [21][22][23][24].…”
Section: Analyses Of Extractsmentioning
confidence: 99%
“…The equipment used for the PEF treatment is provided in detail in our previous studies [19,20,23]. In brief, the was comprised of a high voltage power generator (Leybold, LD Didactic GmbH, Huerth, Germany), a digital oscilloscope, a function/arbitrary waveform generator, and a treatment chamber made of two stainless steel plates (10 cm length and 10 cm height) and 1 cm Teflon between them for isolation purposes.…”
Section: Instrumentationmentioning
confidence: 99%
“…PEF is an extraction technique, based on electro-permeabilization, aiming at the creation of pores in the cellular membranes, and thus, assist in the extraction of compounds. Owing to its inherent advantages, PEF has been successfully employed for the improved extraction of polyphenols from citrus fruits [21], potato peels [22], Sideritis raiseri [23], Merlot grapes [24], etc. Moreover, it has been shown that the use of PEF in combination with ultrasound can increase the extraction of phenolics from plant by-products [25].…”
Section: Introductionmentioning
confidence: 99%